'Information is information': a public perspective on incidental findings in clinical and research genome‐based testing. (3rd May 2013) - Daack‐Hirsch, S; Driessnack, M; Hanish, A; Johnson, VA; Shah, LL; Simon, CM; Williams, JK
<x xml:space="preserve">Abstract</x> The potential for genomic incidental findings is increasing with the use of genome‐based testing. At the same time approaches to clinical decision making are shifting to shared decision‐making models involving both the healthcare community and the public. The public's voice has been nearly absent in discussions on managing incidental findings. We conducted nine focus groups and nine interviews (n = 63) with a broad cross‐section of lay public groups to elucidate public viewpoints on incidental findings that could occur as a result of genome‐based testing in clinical and research situations. Data were analyzed using qualitative content analysis. Participants wanted incidental findings disclosed to them whether or not these were clinical or research findings. Participants used different terms to define and describe incidental findings; they wanted to know that incidental findings are possible and be given a choice to learn about them. Personal utility was an important reason for disclosure, and participants believed that managing information is a shared responsibility between professionals and themselves. Broad public input is needed in order to understand and incorporate the public's perspective on management of incidental findings as disclosure guidelines, and policies are developed in clinical and research settings.